2015
DOI: 10.1002/jrs.4723
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman analysis of pigments from hunter–gatherer archaeological sites of North Patagonia (Argentina)

Abstract: In Northwestern Patagonia, many archaeological sites can be found that testify human occupation by hunter-gatherer groups during the Holocene period. The general purpose of archaeological research in this area is to obtain information on the movements of these groups between the dry steppe and the different sectors in the forests. This paper reports on the results of the first spectroscopic analysis of samples from the archaeological excavation of two hunter-gatherer regions in Northern Patagonia (Traful Lake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 43 publications
2
27
0
2
Order By: Relevance
“…Furthermore, pigments found on leather artefacts from the archaeological site Campo Moncada 2 (Piedra Parada, Chubut province) were analysed with Raman spectroscopy by Bellelli et al . Finally, in 2015, Rousaki et al . reported the analysis of pigments, beads, grinding tools and pottery from archaeological excavation of hunter‐gatherer archaeological sites from Traful Lake (Neuquén province) and Manso River areas (Río Negro province) using the combination of micro‐Raman spectroscopy and X‐ray fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pigments found on leather artefacts from the archaeological site Campo Moncada 2 (Piedra Parada, Chubut province) were analysed with Raman spectroscopy by Bellelli et al . Finally, in 2015, Rousaki et al . reported the analysis of pigments, beads, grinding tools and pottery from archaeological excavation of hunter‐gatherer archaeological sites from Traful Lake (Neuquén province) and Manso River areas (Río Negro province) using the combination of micro‐Raman spectroscopy and X‐ray fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…In general, several analytical works have proved that Raman spectrometers equipped with green lasers are particularly suitable for the study of green and blue compounds (such as organic compounds, pigments, corrosions, etc) . On the other hand, the use of red lasers is suggested to study red and yellow compounds . This concept underlines that by using different laser excitation sources in a complementary way, it is possible to maximize the molecular information provided by Raman spectroscopy .…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] On the other hand, the use of red lasers is suggested to study red and yellow compounds. [15,16] This concept underlines that by using different laser excitation sources in a complementary way, it is possible to maximize the molecular information provided by Raman spectroscopy. [17] The veracity of this statement is further corroborated in this work, because the combined use of different Raman systems has been defined as the analysis protocol for the characterization of different kind of archaeometallurgical artefacts.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of associated minerals and silicates indicated that clay‐like material (ochre) was used, instead of pure haematite. Although not fully conclusive, Raman spectroscopic results tend to indicate that in some samples haematite might be formed by heating iron‐containing ochres …”
Section: Art and Archaeologymentioning
confidence: 99%